The structural factors affecting the sensory properties of polyaniline derivatives. Issue 14 (22nd June 2022) - Andriianova, Anastasia N.; Salikhov, Renat B.; Latypova, Lyaysan R.; Mullagaliev, Ilnur N.; Salikhov, Timur R.; Mustafin, Akhat G.
Abstract : This study is the first report that includes the experimental data on the use of a wide range of new substituted polyaniline (PANI) derivatives as a sensitive material in sensors. Abstract : Humidity control and monitoring are of great interest for a wide range of applications, including moisture-sensitive products, storage of medicines, and environmental monitoring for keeping valuable antiques or paintings . In this regard, the research priority is the development of a sensitive material for humidity sensors that ensure high performance and sensitivity, and can operate at room temperature as well. Electrically conductive polymers are the most promising candidates among the materials used for humidity sensors. This study is the first report that includes the experimental data on the use of a wide range of new substituted polyaniline (PANI) derivatives as a sensitive material in sensors. The influence of various structural factors such as environmental conditions, the position and number of substituents, and the nature of the doping agent on the sensitivity of polymer materials to changes in humidity was studied. It was found that the use of PANI derivatives as a sensitive material in resistive sensors resulted in a high electrical conductivity response to changes in humidity (% RH). N -substituted and Cl-containing ortho -substituted PANIs showed the smallest response compared to bulky alkyl and cyclo-alkyl substituted polymers, which demonstrated the highest response. In addition, the PANI derivative-based sensors exhibited humidity sensing properties in the broad humidity range of 20–90%. The presented results demonstrate that the modification of PANI by introducing a substituent into the aromatic ring not only improves the solubility but also increases the sensitivity of the material to environmental humidity due to the formation of a porous structure with a large surface area.